Peningkatan Hasil Belajar Siswa Menggunakan Model Discovery Learning Berbantuan Media Audio Visual pada Pendidikan Agama Katolik di kelas IV SDN 08 Semidang - Stefanus Stefanus (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
In Dusun Semidang, Desa Suka Maju, Kecamatan Sungai Betung, Kabupaten Bengkayang, West Kalimantan Province, education faces significant challenges. The majority of the population, engaged in farming and gardening, has a low level of education, especially after completing elementary school. The low educational attainment of parents can influence their understanding of the importance of education for their children. This research focuses on Catholic Religious Education at SDN 08 Semidang, with the aim of shaping students into individuals of faith. Students have low interest in learning, lack access to textbooks, and receive inadequate family support. In the fourth grade of SDN 08 Semidang, the Discovery Learning method with the assistance of audio-visual media is applied to address these issues.This study uses two action cycles based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection phases. In the first cycle, student learning outcomes did not meet the target, but student reflection questionnaires indicated improvement. In the second cycle, the results were better, with student attitudes reaching 83% of the 80% target. Therefore, the second cycle is considered sufficient and concluded.The results show that the discovery learning model with audio-visual media is effective in improving the learning outcomes of Catholic Religious Education and Character Education in the fourth grade at SDN 08 Semidang. Several recommendations are proposed for further development, including designing more contextual learning materials, providing teacher training, continuous evaluation, active parental participation, and further research to assess the long-term impact of this learning model..